2018
DOI: 10.1002/gps.4893
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and functional progression in Alzheimer disease: A prediction model of latent classes

Abstract: Objective We sought to replicate a previously published prediction model for progression, developed in the Cache County Dementia Progression Study (CCDPS), using a clinical cohort from the National Alzheimer’s Coordinating Center. Methods We included 1120 incident AD cases with at least one assessment after diagnosis, originating from 31 Alzheimer Disease centers from the United States. Trajectories of the Mini-Mental State Examination (MMSE) and Clinical Dementia Rating sum of boxes (CDR-sb) were modeled jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 46 publications
7
39
3
Order By: Relevance
“…In accordance with previous studies, we observed great heterogeneity in the longitudinal course of dementia . In both our samples, a clear correlation was observed between MMSE and IADL trajectories (NACC: r = .61, P < .001; 4C: r = .79, P < .001).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In accordance with previous studies, we observed great heterogeneity in the longitudinal course of dementia . In both our samples, a clear correlation was observed between MMSE and IADL trajectories (NACC: r = .61, P < .001; 4C: r = .79, P < .001).…”
Section: Discussionsupporting
confidence: 91%
“…Haaksma et al subsequently conducted a replication of Leoutsakos' study, using the same measurement scales in a sample from the National Alzheimer's Coordinating Center (NACC) (N = 1120). This replication study yielded three latent trajectories . A recent study based on a sample of incident dementia cases derived from two Swedish population‐based cohorts identified two distinct trajectories of MMSE and activities of daily functioning .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Fifth, the K-MMSE we used in the present study is a relatively crude assessment of cognitive function. 43 Thus, subtle changes in cognitive function may be undetectable with this tool. Lastly, although we adjusted for chronic health conditions in our analyses, certain chronic diseases may be closely related to cognitive function among older adults.…”
Section: Growth Curve Model Resultsmentioning
confidence: 99%
“…Fourth and relatedly, the KLoSA datasets do not contain information regarding whether the spousal death was expected or unexpected, which may influence the impact of widowhood. Fifth, the K‐MMSE we used in the present study is a relatively crude assessment of cognitive function . Thus, subtle changes in cognitive function may be undetectable with this tool.…”
Section: Discussionmentioning
confidence: 97%